2013
DOI: 10.1080/17429145.2012.672660
|View full text |Cite
|
Sign up to set email alerts
|

Genistin and quinolizidine alkaloid induction inL. angustifoliusaerial parts in response to mechanical damage

Abstract: Lupinus species are commonly used as annual forage and for grain production. They are considered alternative crops to soybean due to their adaptation to cool environments and dry soils. The present study is an analysis of the chemical changes coming from biomass removal in a sweet genotype of Lupinus angustifolius. Mechanical damage induced significant increases in antioxidant activity (12.4%), as well as in flavonoid and phenolic content (36.6% and 12.0%, respectively). This sweet lupin also exhibited a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…This concept is supported by Hendricks et al (2011) who suggested that phenolic compounds in leaf might be involved in chemical defense of P. australis against herbivores and neighboring plants. In addition, Chludil et al (2012) reported that leaves of Lupinus angustifolias as with most species of Fabaceae are capable of producing chemical defenses against herbivores and pathogenic microorganisms that facilitate the biological invasion of those species. Secondly, P. australis-dominated ecosystems produce large volumes of above and belowground biomass (Park & Blossey 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This concept is supported by Hendricks et al (2011) who suggested that phenolic compounds in leaf might be involved in chemical defense of P. australis against herbivores and neighboring plants. In addition, Chludil et al (2012) reported that leaves of Lupinus angustifolias as with most species of Fabaceae are capable of producing chemical defenses against herbivores and pathogenic microorganisms that facilitate the biological invasion of those species. Secondly, P. australis-dominated ecosystems produce large volumes of above and belowground biomass (Park & Blossey 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of grazing on plant communities and ecosystems are determined by the responses of individual species; the dominant species play an especially crucial role (Smith and Knapp ). For the individual plants, injury by grazing can cause a wide range of metabolic and physiological responses (Peng et al , Chludil et al ). Leaves are the main organs of assimilation in plants, so disruption of the leaves can increase water loss and change CO 2 assimilation and nutrient concentrations (Oleksyn et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Quinolizidine alkaloids are typically inducible compounds (Chludil et al 2013;Wink 1983), but may accumulate after more than 48 hours. For example, in other Lupinus species, alkaloid induction occurred 72 hours after damage (Vilarino et al 2005).…”
Section: Does Herbivory Induce Changes In Phytohormones and Alkaloid mentioning
confidence: 99%